Pelagic amphipods (Crustacea: Amphipoda: Hyperiidea) in western Mexico. 7. Superfamily Platysceloidea. Family Oxycephalidae - Gasca, Rebeca; Hendrickx, Michel E. (Zootaxa, 2022)
Twelve species of the family Oxycephalidae were collected during a deep-water survey off western Mexico: four species of Rhabdosoma, three species of Streetsia, two species of Oxycephalus, and one species each of Cranocephalus, Glossocephalus, and Leptocotis. In total, 321 specimens were collected, 114 males and 207 females, in 33 sampling localities in the Gulf of California (28) and off southwestern Mexico (5). Two species dominated in the samples and co-occurred in 17 of the 33 samples containing hyperiids: Oxycephalus clausi (24 localities, 152 specimens) and Rhabdosoma whitei (20 localities, 121 specimens). Considering this study and previous records, a total of 16 of the 18 described species of Oxycephalidae (89%) have been reported from western Mexico. Distribution of this new material off western Mexico is provided together with update data on species occurrence in the eastern Pacific.